Decreased miR-4512 Levels in Monocytes and Macrophages of Individuals With Systemic Lupus Erythematosus Contribute to Innate Immune Activation and Neutrsophil NETosis by Targeting TLR4 and CXCL2 - Yang, Binbin; Huang, Xinwei; Xu, Shuangyan; Li, Li; Wu, Wei; Dai, Yunjia; Ge, Ming-Xia; Yuan, Limei; Cao, Wenting; Yang, Meng; Wu, Yongzhuo; Deng, Danqi (Frontiers in Immunology, 2021)
Objective: Systemic lupus erythematosus (SLE) is an autoimmune disease with complex etiology that is not yet entirely understood. We aimed to elucidate the mechanisms and therapeutic potential of microRNAs (miRNAs) in SLE in a Tibetan population. Methods: Peripheral blood mononuclear cells from SLE patients (n = 5) and healthy controls (n = 5) were used for miRNA–mRNA co-sequencing to detect miRNAs related to immune abnormalities associated with SLE. Luciferase reporter assay was used to identify potential targets of candidate miRNA. The target genes were verified in miRNA-agomir/antagomir transfection assays with multiple cells lines and by expression analysis. The effects of candidate miRNA on monocyte and macrophage activation were evaluated by multiple cytokine profiling. Neutrophil extracellular traps (NETs) formation was analyzed in vitro by cell stimulation with supernatants of monocytes and macrophages transfected with candidate miRNA. The rodent MRL/lpr lupus model was used to evaluate the therapeutic effect of CXCL2Ab on SLE and the regulation effect of immune disorders. Results: Integrated miRNA and mRNA expression profiling identified miRNA-4512 as a candidate miRNA involved in the regulation of neutrophil activation and chemokine-related pathways. MiR-4512 expression was significantly reduced in monocytes and macrophages from SLE patients. MiR-4512 suppressed the TLR4 pathway by targeting TLR4 and CXCL2. Decreased monocyte and macrophage miR-4512 levels led to the expression of multiple proinflammatory cytokines in vitro. Supernatants of miR-4512 antagomir-transfected monocytes and macrophages significantly promoted NETs formation (P < 0.05). Blocking of CXCL2 alleviated various pathogenic manifestations in MRL/lpr mice, including kidney damage and expression of immunological markers of SLE. Conclusions: We here demonstrated the role of miR-4512 in innate immunity regulation in SLE. The effect of miR-4512 involves the regulation of monocytes, macrophages, and NETs formation by direct targeting of TLR4 and CXCL2, indicating the miR-4512-TLR4-CXCL2 axis as a potential novel therapeutic target in SLE.